Peran Pelatihan dan Keterikatan Kerja Untuk Meningkatkan Kinerja Karyawan Pada Industri Telekomunikasi - Ruhiyat, Imam; Meria, Lista; Julianingsih, Dwi (Technomedia Journal, 2022)
This research was conducted with the aim of knowing the role of training, work engagement on employee performance for employees in the Telecommunication Service Provision Industry who reside in the Greater Jakarta area. The independent variable is training, work engagement, while the dependent variable is employee performance. The population in this study are employees who live in the Greater Jakarta area who work in telecommunications service companies. The number of samples contained in this study were 200 respondents. The sampling technique contained in this study uses a non-probability sampling method with purposive sampling technique, the data instrument testing uses validity and reliability tests. The method used in this research is Structural Equation Modeling (SEM). Based on this research, it was found that training had a positive and significant effect on employee performance. Furthermore, training has a positive and significant effect on work engagement. Then the work engagement has a positive and significant effect on employee performance. Keywords: Training, Work Engagement, Employee Performance.